2023
DOI: 10.3390/agronomy13082112
|View full text |Cite
|
Sign up to set email alerts
|

Plant–Nanoparticle Interactions: Transcriptomic and Proteomic Insights

Neelma Munir,
Wafa Gulzar,
Zainul Abideen
et al.

Abstract: In recent years, the relationship between plants and nanoparticles (NPs) has been the subject of extensive research interest. Hence, an ever-increasing number of perspectives connected with both the positive and adverse consequences of NPs application in plants are highlighted in this review. On the other hand, nanoparticles and their interactive effects on plants have raised concern regarding their harmful aspects. There are complex mechanisms evolved in plants for controlling the uptake, accumulation, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 160 publications
0
1
0
Order By: Relevance
“…7,8 NPs can penetrate plant cells and enter plant tissues through various processes, including ion channel transport, passive transport, co-transport of water channel proteins and water molecules, endocytosis, transport by means of carrier proteins, and binding to organic matter. 9,10 Previous studies have reported on the absorption and accumulation of different NPs by plant root cells, 11,12 showing that NPs and their aggregates are only available in the range of the cell wall (CW) aperture (5–30 nm) for uptake by the plant into the cytoplasm of root cells and subsequently move and bind to the CW. 13,14 After crossing the plant CW, NPs accumulate in various subcellular locations within the cell, such as the cell membrane, vesicles, and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 NPs can penetrate plant cells and enter plant tissues through various processes, including ion channel transport, passive transport, co-transport of water channel proteins and water molecules, endocytosis, transport by means of carrier proteins, and binding to organic matter. 9,10 Previous studies have reported on the absorption and accumulation of different NPs by plant root cells, 11,12 showing that NPs and their aggregates are only available in the range of the cell wall (CW) aperture (5–30 nm) for uptake by the plant into the cytoplasm of root cells and subsequently move and bind to the CW. 13,14 After crossing the plant CW, NPs accumulate in various subcellular locations within the cell, such as the cell membrane, vesicles, and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%